How Is Mental Health Nursing Research Evolving? Advancing Collaboration, Community-Based Care, and Digital Mental Health Interventions - Suara, Mahyar; Putri, Adelia; Putri, Natasyha Amalia Eka; Sintia, Putri Della; Faozy, Naomy Gita (Chakra Brahmanda Lentera Institute, 2026)
Background: Mental health disorders represent a major global public health challenge and significantly affect quality of life and healthcare systems. Mental health nursing research has expanded rapidly in response to increasing global mental health needs. However, comprehensive bibliometric mapping of global research trends and collaboration networks in mental health nursing research remains limited. This study aimed to analyze global publication trends, research productivity, and collaboration networks in mental health nursing research indexed in Scopus. Methods: This study employed a bibliometric analysis approach informed by systematic review procedures. Data were retrieved from the Scopus database. The search included publications from 2000 to 2024. A total of 275 publications that met the eligibility criteria were included in the analysis. Bibliometric indicators analyzed included annual publication growth, citation patterns, co-authorship networks, and keyword co-occurrence. Metadata such as authors, institutions, countries, publication year, and keywords were extracted and organized for analysis. Network visualization and bibliometric mapping were performed using VOSviewer version 1.6.18. Results: The analysis identified 275 publications on mental health nursing research, demonstrating a notable increase in research output after 2022. Bibliometric mapping revealed several thematic clusters related to mental health disorders, psychological stress, social support, digital mental health interventions, and community-based mental health care. Collaboration network analysis showed increasing international research partnerships among authors, institutions, and countries, highlighting the growing importance of global collaboration in advancing mental health nursing knowledge. Conclusion: Mental health nursing research has experienced substantial growth globally, particularly in recent years. Bibliometric findings highlight the importance of international collaboration and interdisciplinary research in addressing global mental health challenges. Future studies should strengthen collaborative networks and focus on emerging research themes such as digital mental health interventions, community-based care, and culturally responsive mental health services to support evidence-based nursing practice and policy development.